Effect of Swirl Strength on the Flow and Combustion Characteristics of Pulverized Biomass Flames. Issue 4 (3rd April 2019) - Elorf, Abdallah; Sarh, Brahim; Tabet, Fouzi; Bostyn, Stéphane; Asbik, Mohamed; Bonnamy, Sylvie; Chaoufi, Jamal; Boushaki, Toufik; Gillon, Pascale
ABSTRACT: This article reports on the effect of swirl intensity on the flow and combustion characteristics of pulverized olive waste (OW) burning. Numerical simulations are carried out using the computational fluid dynamics (CFD) Commercial Software "Fluent ANSYS14" by choosing appropriate model parameters. The biomass furnace consists of a vertical cylinder equipped with a swirling co-flow injection burner. The particles of pulverized biomass (OW) are injected transversally into the furnace just near the co-flow exit, via four square-shaped injection nozzles. The non-premixed combustion model with mixture fraction/PDF model for turbulence-chemistry interactions is used. Standard k-ε turbulence model closure, discrete phase model (DPM) for tracking the motion of individual particle and P-1 radiation model for flame radiation inside the combustor are used in the numerical simulation. Four different swirl numbers Sn  = 0.38, 0.95, 1.2 and 1.42 are used in this study in order to investigate the swirl intensity effect on the flow and combustion behavior. The results showed that the flow and the flame characteristics such as axial velocity, streamlines, gas temperature, flame length and CO2, CO and O2 concentrations are affected by the swirl intensity.